2017
DOI: 10.1177/1403494817733869
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in Europe: Health-related and sociodemographic determinants

Abstract: Aims: The aim of this research was to study health-related and sociodemographic determinants of the use of different complementary and alternative medicine (CAM) treatments in Europe and differences in CAM use in various European countries. Methods: The study was based on a design-based logistic regression analysis of the European Social Survey (ESS), Round 7. We distinguished four CAM modalities: manual therapies, alternative medicinal systems, traditional Asian medical systems and mind-body therapies. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
244
1
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(298 citation statements)
references
References 29 publications
33
244
1
20
Order By: Relevance
“…These results were mostly replicated in the subgroup analysis of CAM treatments, with the exception that financial strain and employment were found to be significant predictors of physical but not consumable CAM use. Prior studies have found greater CAM use among females [10,32,33]. Females have been found to report higher rates of unmet need [18], more health care utilization [34] and poorer health [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were mostly replicated in the subgroup analysis of CAM treatments, with the exception that financial strain and employment were found to be significant predictors of physical but not consumable CAM use. Prior studies have found greater CAM use among females [10,32,33]. Females have been found to report higher rates of unmet need [18], more health care utilization [34] and poorer health [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, females, those in higher socioeconomic groups and those of middle age, have all been found to be more frequent users of CAM [8,9]. More recent work has examined the health-related and sociodemographic determinants of CAM treatments specifically in Europe, finding that use of CAM is greater among those with health problems, and more common among women and those with a higher education [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrative health therapies are whole person, person-centered, and relationship-based approaches encompassing biomedical and nonbiomedical therapies based on scientific evidence for optimal health and well-being [1,2]. Surveys indicated that the prevalence of IH therapy use among adults was 33.2%, 25.9%, and 63.1% in the U.S., European countries, and Australia, respectively [3][4][5]. Integrative health therapies are especially sought by patients with chronic conditions for preventing future health problems, expanding treatment options, and maximizing well-being [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Avrupa genelinde toplanan 2014 yılı verilerine göre yapılan benzer bir çalışmada, 12 aylık süreçte tamamlayıcı ve alternatif yöntemlerin kullanımı sorgulanmış ve çalışılan popülasyonun %25,9'unun bu tedavi modalitelerinden birini kullandığı izlenmiştir. 3 Bu çalışma incelendiğinde, Avrupa'da tamamlayıcı ve alternatif tedaviler olarak tanımlanan bu tür uygulamaların yaygın bir şekilde kullanıldığı görülmektedir. Bu uygulamalar sadece koruyucu hekimlikte değil tedavi maksadıyla da tercih edilmektedir.…”
Section: Temel Dayanakunclassified